Search for Higgs and Z boson decays to J/psi or Y pairs in the four-muon final state in proton-proton collisions at root s=13 TeV - (:unkn) unknown (ELSEVIER, 2019)
A search for decays of the Higgs and Z boson to pairs of J/psi or Y(nS)(n = 1, 2, 3) mesons, with their subsequent decay to mu(+)mu(-) pairs, is presented. The analysis uses data from proton-proton collisions at root s = 13 TeV, collected with the CMS detector at the LHC in 2017 and corresponding to an integrated luminosity of 37.5 fb(-1). While an observation of such a decay with this sample would indicate the presence of physics beyond the standard model, no significant excess is observed. Upper limits at 95% confidence level are placed on the branching fractions of these decays. In the J/psi pair channel, the limits are 1.8 x 10(-3) and 2.2 x 10(-6) for the Higgs and Z boson, respectively, while in the combined Y(nS) pair channel, the limits are 1.4 x 10(-3) and 1.5 x 10(-6), respectively, when the mesons from the Higgs and Z boson decay are assumed to be unpolarized. When fully longitudinal and transverse polarizations are considered the limits reduce by about 22-29% and increase by about 10-13%, respectively. (C) 2019 The Author(s). Published by Elsevier B.V.
Keywords: CMS; Standard model physics; Higgs boson; Z boson; Rare decays; ; PARTON DISTRIBUTIONS; QUARK MASSES; HIERARCHY; LHC